(3GdaUjMs - (3CHh GdYHGS CMeO Hf jMji Hf RjO KYdH GdTjHGfj Gdchaj GdfMhj,J (B291 (3g` s
(3ChdgG (B:s
(3gPG cJGH GNJjGQ aUjM GdcdGe eeG jLQi ai cdGe GdfGS s
(3BNQgG (B:s
(3Je GdcJGH efbhd ef NW CHj GdMSf GdSeSei GddZhi HMhGTjg MQaG MQaGq s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B252s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1272s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GddZIs